VERVE-FORECAST FVS-9510, SOUNDS OF AFRICA. One 12-inch Stereo L.P. from the A.B.C. News, Television Production, "Africa”, edited by Andrew Tracey. (International Library of African Music, 1969)
This is a selection from "the many hours of music” recorded by the "Africa Project” teams of the A.B.C. Television News. In June, 1966, they sent no less than "ten camera crews to Africa to make a full-length feature film covering every aspect of modern Africa - everything from politics to big-game. Eight months and more than a million dollars later they came back with probably the most fascinating and complete film coverage of a continent ever made.”
Keywords: African Music